Removal of chromium by continuous flow using wool packed columns - Manassra, Adnan (2010)
Wool was utilized for the removal of Cr from aqueous solution. The wool fibers exhibited selective removal of Cr(VI) at pH 1.0. Breakthrough curves showed that wool can absorb Cr(VI) up to the maximum range studied (600 mg /26 g) without saturation. The removal efficiency was found to be independent of the flow rate (between 2.3 and 6 mL/min) and the wool fiber length. Temperature was found to enhance the de-sorption process. The percentage of removal increased from 84% to 97% by increasing the Cr(VI) initial concentration from 5 ppm to 200 ppm. The results suggest cooperative binding of Cr(VI) to different binding sites on wool, or structural changes of the wool upon Cr(VI) binding. The affinity of wool sites for binding of Cr(VI) depends on local variations in pH leading to two distinguished modes. The first mode is reversible binding accompanied with small enthalpy change indicating physisorption. The second mode is irreversible with strong electrostatic interactions indicating chemisorption.